2021
DOI: 10.26858/ijole.v5i1.14917
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Teaching Lexical Bundles on EFL Students’ Abstract Genre Academic Writing Skills Improvement: Corpus-Based Research Design

Abstract: Lexical bundles are two or more string of words that co-occur frequently in a corpus. Hence, this corpus-based research design study examines the effects of lexical bundles on English as a foreign language learner’s abstract genre academic writing skills, and it also investigates students’ perception towards lexical bundles instruction to enhance their academic writing skills. Hence, frequent lexical bundles were selected from 70 computer science articles. These articles were selected from 7 journals that were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 43 publications
(63 reference statements)
1
5
0
Order By: Relevance
“…The results of the study revealed that the instruction of lexical bundles significantly develops Turkish prospective EFL teachers' writing skills in terms of accuracy and appropriacy. The findings of the present study were aligned with the literature (Kazemi et al, 2014;AlHassan & Wood, 2015;Latifi & Afraz, 2015;El-Dakhs et al, 2017;Nemati, 2019;Kanglong & Afzaal, 2020;Yilmaz & Koc, 2020;Birhan, 2021) that concluded that explicit instruction of lexical bundles significantly affected the writing abilities of learners.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results of the study revealed that the instruction of lexical bundles significantly develops Turkish prospective EFL teachers' writing skills in terms of accuracy and appropriacy. The findings of the present study were aligned with the literature (Kazemi et al, 2014;AlHassan & Wood, 2015;Latifi & Afraz, 2015;El-Dakhs et al, 2017;Nemati, 2019;Kanglong & Afzaal, 2020;Yilmaz & Koc, 2020;Birhan, 2021) that concluded that explicit instruction of lexical bundles significantly affected the writing abilities of learners.…”
Section: Discussionsupporting
confidence: 91%
“…The study revealed that explicit lexical bundle education had a substantial impact on 34 undergraduate students' writing abilities. Birhan (2021) examined how lexical bundles impact academic writers of abstract genres who are learning English as a second language. The author also considers students' attitudes toward learning lexical bundles to enhance their academic writing skills.…”
Section: Conceptual Backgroundmentioning
confidence: 99%
“…The instruction offers viable linguistic resources such as lexical bundles (phraseology units) and metadiscourse devices that students use in their communicative situations. In academic writing, researchers (Birhan, 2021;Shirazizadeh & Amirfazlian, 2021) reported that these linguistic features occur frequently in different academic writing genres, and they facilitate communication between a reader and a writer. Thus, to enhance students' engagement in the teaching and learning process, students should be instructed via an instructional approach which embeds authentic linguistic features.…”
Section: Corpus-based Instruction and Students' Engagementmentioning
confidence: 99%
“…Different issues on academic writing are raised in several studies: grammar and lexical bundles (Akbulut, 2020;Birhan, 2021), methodology for teaching academic writing (Kwak, 2017;Hussain, 2019), error analysis (Benjamin, 2017), digital resources support (Åberg et al, 2016;Alresheedi, 2019;Bezus et al, 2021;Strobla et al, 2019), etc. However, the researchers draw little attention to the punctuation as a particular side of academic writing skills (Al-Tamimi, 2018;Ali et al, 2020;Alharthi, 2021).…”
Section: Research Articlementioning
confidence: 99%
“…Various studies have focused on how foreign students can improve their academic writing skills in English. Thus, R. Esfandiari & F. Barbary (2017), A. T. Birhan (2021) propose to develop students' academic writing skills with the help of lexical bundles.…”
Section: Literature Reviewmentioning
confidence: 99%